Neutralizing Autoantibodies to Type I IFNs in >10% of Patients with Severe COVID-19 Pneumonia Hospitalized in Madrid, Spain. - Troya, Jesús; Bastard, Paul; Planas-Serra, Laura; Ryan, Pablo; Ruiz, Montse; de Carranza, María; Torres, Juan; Martínez, Amalia; Abel, Laurent; Casanova, Jean-Laurent; Pujol, Aurora (J Clin Immunol, 2021)
BACKGROUND: In a recent study, autoantibodies neutralizing type I interferons (IFNs) were present in at least 10% of cases of critical COVID-19 pneumonia. These autoantibodies neutralized most type I IFNs but rarely IFN-beta. OBJECTIVES: We aimed to define the prevalence of autoantibodies neutralizing type I IFN in a cohort of patients with severe COVID-19 pneumonia treated with IFN-beta-1b during hospitalization and to analyze their impact on various clinical variables and outcomes. METHODS: We analyzed stored serum/plasma samples and clinical data of COVID-19 patients treated subcutaneously with IFN-beta-1b from March to May 2020, at the Infanta Leonor University Hospital in Madrid, Spain. RESULTS: The cohort comprised 47 COVID-19 patients with severe pneumonia, 16 of whom (34%) had a critical progression requiring ICU admission. The median age was 71 years, with 28 men (58.6%). Type I IFN-alpha- and omega-neutralizing autoantibodies were found in 5 of 47 patients with severe pneumonia or critical disease (10.6%), while they were not found in any of the 118 asymptomatic controls (p = 0.0016). The autoantibodies did not neutralize IFN-beta. No demographic, comorbidity, or clinical differences were seen between individuals with or without autoantibodies. We found a significant correlation between the presence of neutralizing autoantibodies and higher C-reactive protein levels (p = 5.10e) and lower lymphocyte counts (p = 1.80e). No significant association with response to IFN-beta-1b therapy (p = 0.34) was found. Survival analysis suggested that neutralizing autoantibodies may increase the risk of death (4/5, 80% vs 12/42, 28.5%). CONCLUSION: Autoantibodies neutralizing type I IFN underlie severe/critical COVID-19 stages in at least 10% of cases, correlate with increased C-RP and lower lymphocyte counts, and confer a trend towards increased risk of death. Subcutaneous IFN-beta treatment of hospitalized patients did not seem to improve clinical outcome. Studies of earlier, ambulatory IFN-beta treatment are warranted.